2007
DOI: 10.1007/s10517-007-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant plasmid constructs expressing gene for antimicrobial peptide melittin for the therapy of mycoplasma and chlamydia infections

Abstract: In view of growing number of pathogenic microbial strain resistant to routine antibiotics, antimicrobial peptides become promising agents for the therapy of infectious diseases. We studied in vivo effects of melittin, an antimicrobial peptide expressed in a recombinant plasmid vector, on infection with urogenital pathogens Chlamydia trachomatis, Mycoplasma hominis, and Mycoplasma gallisepticum. We obtained recombinant plasmid constructs, where melittin gene is under the control of tetracycline-dependent human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In vitro studies have demonstrated its antibacterial activity against a wide range of microorganisms [ 19 , 73 , 89 , 90 ]. In vivo studies also provide evidence for the antibacterial activity of melittin against Chlamydia trachomatis [ 91 ], Cutibacterium acnes [ 92 ], MRSA [ 49 ] and extensively drug-resistant (XDR) A. baumannii [ 93 ]. Antibacterial properties of BV and melittin seem promising, especially for multidrug-resistant (MDR) bacteria [ 48 ].…”
Section: Antimicrobial Properties Of Bee Productsmentioning
confidence: 99%
“…In vitro studies have demonstrated its antibacterial activity against a wide range of microorganisms [ 19 , 73 , 89 , 90 ]. In vivo studies also provide evidence for the antibacterial activity of melittin against Chlamydia trachomatis [ 91 ], Cutibacterium acnes [ 92 ], MRSA [ 49 ] and extensively drug-resistant (XDR) A. baumannii [ 93 ]. Antibacterial properties of BV and melittin seem promising, especially for multidrug-resistant (MDR) bacteria [ 48 ].…”
Section: Antimicrobial Properties Of Bee Productsmentioning
confidence: 99%
“…The AMPs are among the compounds under investigation for their general antimicrobial potency, and several of them are undergoing clinical evaluation (29,30). Regarding the Mollicutes, a recombinant plasmid expressing a gene for an AMP, melittin, was introduced into cell line and animal models, and the results suggested efficacy in the treatment of infections caused by Mycoplasma hominis and Mycoplasma gallisepticum (31)(32)(33)(34). Our study may provide another promising new strategy for treating ureaplasma infections.…”
Section: Discussionmentioning
confidence: 86%
“…Some peptides consist of short amino acid chains that are common antibacterial protein compounds (Yasin et al, 2004). Lazarev et al explored the use of the antimicrobial peptide melittin in treating chlamydia infections, the main active ingredient in bee venom, in the mid-1990s (Lazarev et al, 2002(Lazarev et al, , 2005(Lazarev et al, , 2007. C. trachomatis was inhibited in vitro by introducing and activating a recombinant plasmid vector expressing the melittin gene.…”
Section: Peptidesmentioning
confidence: 99%